2020
DOI: 10.48048/wjst.2020.3630
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Resilience Enhancing Nursing Program on Depression among Pregnant Teenagers

Abstract: The purposes of this study were to evaluate the effects of the resilience enhancing nursing program (RENP) on resilience and depression among pregnant teenagers who received this program. A quasi experimental was conducted with 130 pregnant Thai women. Final analysis included 130 participants (Intervention n = 64 and control group n = 66). The RENP was delivered in three steps including; Step 1, establishing trusting relationships; Step 2, improving the resilience, and Step 3, monitoring and encouraging the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…The experience of negative emotions such as feelings of stigma, shame, guilt, helplessness and loneliness was also significantly lower among those with high resilience. This finding was comparable to a previous study where resilience has been reported to help increase pregnant teenagers’ capacity to overcome adversities from a crisis situation such as the damaging effects of unintended pregnancies 35 . Resilience is also an enabling factor for healthcare service engagement among young mothers even in the face of stigma or negative stereotype from healthcare providers 14 .…”
Section: Discussionsupporting
confidence: 85%
“…The experience of negative emotions such as feelings of stigma, shame, guilt, helplessness and loneliness was also significantly lower among those with high resilience. This finding was comparable to a previous study where resilience has been reported to help increase pregnant teenagers’ capacity to overcome adversities from a crisis situation such as the damaging effects of unintended pregnancies 35 . Resilience is also an enabling factor for healthcare service engagement among young mothers even in the face of stigma or negative stereotype from healthcare providers 14 .…”
Section: Discussionsupporting
confidence: 85%
“…This motivated the researcher to examine the effectiveness of social skills training on enhancing self-concept of teenage mothers in that location to increase their self -concept. According to Kuasit et al (2018), a study location is selected because of existence of a problem.…”
Section: Methodsmentioning
confidence: 99%
“…This is relevant to the study as it brought out clearly the significant association between social skills and relationship management among teenage girls, which could also apply to self-concept among teenage mothers in Kenya adopting mixed method sequential explanatory design. Kuasit, Chunuan, Hatthakit, and Bullock (2018) conducted a study in China to evaluate the effectiveness of Nursing Program as a strategy in enhancing and building resilience in pregnant teenagers. The findings revealed that the participants in the experimental group had a significantly greater improvement in mean score of life goals than did the control group.…”
Section: Literature Reviewmentioning
confidence: 99%